2014
DOI: 10.1038/ncomms4573
|View full text |Cite
|
Sign up to set email alerts
|

One-dimensional self-confinement promotes polymorph selection in large-area organic semiconductor thin films

Abstract: A crystal's structure has significant impact on its resulting biological, physical, optical and electronic properties. In organic electronics, 6,13(bis-triisopropylsilylethynyl)pentacene (TIPS-pentacene), a small-molecule organic semiconductor, adopts metastable polymorphs possessing significantly faster charge transport than the equilibrium crystal when deposited using the solution-shearing method. Here, we use a combination of high-speed polarized optical microscopy, in situ microbeam grazing incidence wide-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
166
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 137 publications
(174 citation statements)
references
References 48 publications
(68 reference statements)
4
166
1
Order By: Relevance
“…As expected, both absorption features decrease in intensity during the 30 s spin-casting experiments indicating loss of solute material from the light path, but do not exhibiting any shift in the peak position expected with solid state formation ( Figure S7). The latter observation indicates that diF-TES-ADT remains mostly dissolved and un-aggregated throughout the spin-coating process, [27] which is also confirmed by in situ high-speed polarized optical micrographs (HSPOM) taken during spin-coating [36] ( Figure S8). …”
Section: In-situ Investigation Of the Spin-coating Processmentioning
confidence: 56%
“…As expected, both absorption features decrease in intensity during the 30 s spin-casting experiments indicating loss of solute material from the light path, but do not exhibiting any shift in the peak position expected with solid state formation ( Figure S7). The latter observation indicates that diF-TES-ADT remains mostly dissolved and un-aggregated throughout the spin-coating process, [27] which is also confirmed by in situ high-speed polarized optical micrographs (HSPOM) taken during spin-coating [36] ( Figure S8). …”
Section: In-situ Investigation Of the Spin-coating Processmentioning
confidence: 56%
“…When the evaporation front reaches the trailing electrode, the liquid bridges both the leading electrode and the trailing electrode. Previously, we have shown that crystal growth begins from the air-solvent interface and proceeds toward the substrate during solution shearing (47). In this work, we match the timescale of vertical crystal growth with the lateral crystal growth, to ensure that the crystalline domain that was growing on the leading electrode will extend to the trailing electrode and cover the OTFT channel before the solution dries (see SI Note 1 for a detailed description of this phenomenon).…”
Section: Resultsmentioning
confidence: 99%
“…Nickel and coworkers (30) found that pentacene crystals transition between two polymorphs to reduce the mechanical strain created in the lattice due to differences in contraction/expansion behavior of the film and the substrate. Nanoscale confinement effects during solution processing have also been shown to tune the polymorphism by altering the lattice constants of 6,13-b(triisopropylsilylethynyl)pentacene (TIPS) pentacene films (31). In other studies, the crystals in contact with different surfaces were reported to crack upon cooling, due to strain formation, an effect that was greatly reduced or eliminated with slow cooling (32)(33)(34).…”
Section: Significancementioning
confidence: 99%